Perlakuan Khusus Terhadap Narapidana Lanjut Usia Bidang Kesehatan Pada Lembaga Pemasyarakatan - Marisa Jemmy; Okfa Amin Wendra (Normative Jurnal Ilmiah Hukum, 2025)
Prisoners in correctional institutions not only consist of young and adult detainees and convicts, but also elderly people. In Article 2 paragraph (1) of the Regulation of the Minister of Law and Human Rights Number 32 of 2018 concerning Treatment of Prisoners and Elderly Prisoners, it is stated that special treatment for elderly prisoners or convicts aims to meet the needs of elderly prisoners or convicts so that they can maintain their physical, mental and social abilities. Special Treatment is an effort aimed at providing easy services to help the elderly recover and develop themselves in order to increase their level of social welfare. The formulation of the problem in this research is: first, how is special treatment implemented for elderly prisoners in the health sector in correctional institutions and second, what are the obstacles in implementing special treatment for elderly prisoners in the health sector in correctional institutions. The method used in this research is Sociological Juridical which is descriptive in nature while the data used is primary data and secondary data as well as data collection techniques using field studies, namely library studies, interviews and observations, which are processed using editing and coding processes, then analyzed qualitatively. In reality, the implementation of special treatment in the health sector for elderly prisoners at the Class IIB Solok Correctional Institution has not been implemented well, such as a shortage of medical personnel, the absence of nutritionists and dietitians, a lack of daily equipment, and separate special residential rooms.